2013
DOI: 10.1007/s00520-013-2003-4
|View full text |Cite
|
Sign up to set email alerts
|

Parental depressive symptoms and childhood cancer: the importance of financial difficulties

Abstract: Purpose Research suggests a relationship between caring for a child with cancer and psychological distress in caregivers. Less evident is the role which financial difficulties might play in this relationship. We sought to determine if caring for a child with cancer was related to clinically relevant depressive symptoms among parents, whether or not financial difficulties mediated this relationship, and if financial difficulties were independently associated with symptoms of depression among parents of children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
53
1
7

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 45 publications
7
53
1
7
Order By: Relevance
“…A handful of studies explored the consequences of family financial burden with uniform findings of negative impact on parental and family well‐being. Financial hardship during a child's cancer care was documented to result in increased emotional distress for families, increased burden on parental relationships, and increased risk of serious psychological distress for parents . These findings support a recommendation for standardized efforts to evaluate family financial needs as part of comprehensive psychosocial care in children with cancer.…”
Section: Resultsmentioning
confidence: 65%
See 1 more Smart Citation
“…A handful of studies explored the consequences of family financial burden with uniform findings of negative impact on parental and family well‐being. Financial hardship during a child's cancer care was documented to result in increased emotional distress for families, increased burden on parental relationships, and increased risk of serious psychological distress for parents . These findings support a recommendation for standardized efforts to evaluate family financial needs as part of comprehensive psychosocial care in children with cancer.…”
Section: Resultsmentioning
confidence: 65%
“…Family financial hardship as a consequence of childhood cancer treatment has been documented over the past three decades, and the economic burden of caring for a child with cancer has been described as a significant source of distress for families . Data suggest that financial hardship during childhood cancer treatment has implications for family economic status, parental emotional and mental health, and potentially child well‐being.…”
Section: Introductionmentioning
confidence: 99%
“…Most PCC and families adjust well, and report growth, increased closeness, and good family functioning. Potential resiliency factors include higher socio‐economic status higher levels of social support and higher family cohesion and functioning . Parent attributes such as optimism and use of problem‐solving coping strategies (defined as “sets about solving problems purposefully”, compared to “emotion‐focused coping” and other described coping styles) have also been associated with decreased parental distress.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that while many caregivers demonstrate impressive resilience in the face of a cancer diagnosis, some are at increased risk for post-traumatic stress, depression, anxiety, and somatic illness [6][7][8]. The additional financial burden of treatment may contribute significantly to caregivers' psychological distress [8].…”
Section: Introductionmentioning
confidence: 99%